Adolescent experiences, perceptions, and preferences for the process of HIV status disclosure in Kenya - Mugo, Cyrus; Njuguna, Irene N.; Beima-Sofie, Kristin; Mburu, Caren W.; Onyango, Alvin; Itindi, Janet; Richardson, Barbra A.; Oyiengo, Laura; John-Stewart, Grace; Wamalwa, Dalton C. (Frontiers in Public Health, 2023)
Disclosure of HIV status to adolescents living with HIV has been associated with improved retention in care, antiretroviral adherence, viral suppression, and mental health. The studies on the impact of disclosure have been accompanied by studies among healthcare workers and caregivers describing their disclosure experiences and preferences. There are few studies however that have looked at the experiences, perceptions and preferences for the process of disclosure of HIV status among adolescents and young adults living with HIV themselves, especially in sub-Saharan Africa. This study provides evidence for the need for patient-centered care for adolescents and children undergoing disclosure of their HIV status. It highlights their preferences of early HIV status disclosure, and the need for healthcare worker and caregiver involvement when preparing adolescents for disclosure and providing post-disclosure support. It also demonstrates key outcomes of disclosure from the adolescents' perspective including improvements in adherence, clinic attendance, sexual behavior, communication with healthcare workers and caregivers. The findings reinforce the international and local HIV status disclosure guidelines for children and adolescents that provide an appropriate framework for the disclosure process.